2012
DOI: 10.1097/mca.0b013e3283564869
|View full text |Cite
|
Sign up to set email alerts
|

Improved anemia is associated with favorable long-term clinical outcomes in patients undergoing PCI

Abstract: The follow-up of hemoglobin level is important, and improvement of anemia is associated with favorable long-term clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Anaemia is common amongst patients undergoing percutaneous coronary interventions (PCI) with prevalent rates reported between 10-23% in randomised controlled trials (1-3)and rates greater than 30% reported in observational registries (4,5). Current clinical guidelines fail to offer recommendations for its concurrent management in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia is common amongst patients undergoing percutaneous coronary interventions (PCI) with prevalent rates reported between 10-23% in randomised controlled trials (1-3)and rates greater than 30% reported in observational registries (4,5). Current clinical guidelines fail to offer recommendations for its concurrent management in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…From our real-world PCI registry, the incidence of anemia was 30.5%. The incidence of anemia from other East Asian data was reported as approximately 30%–40%, 20 21 22 which was higher than that in Western countries. 6 23 Current guidelines regarding DAPT duration after PCI are mostly based on large-scale randomized trials and mainly consist of patients without high bleeding risk.…”
Section: Discussionmentioning
confidence: 75%
“…Inflammation is very important in CAD, and low hemoglobin levels is a vital indicator of potential inflammatory processes. Similarly, patients with low hemoglobin levels and subclinical CAD may be more prone to symptomatic heart disease (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%